The relationship between environmental context and attentional engagement in podcast listening experiences - Harrison, Jay; Archer-Boyd, Alan W.; Francombe, Jon; Pike, Chris; Murphy, Damian T. (Frontiers in Psychology, 2023)
Introduction Previous research has shown that podcasts are most frequently consumed using mobile listening devices across a wide variety of environmental, situational, and social contexts. To date, no studies have investigated how an individual's environmental context might influence their attentional engagement in podcast listening experiences. Improving understanding of the contexts in which episodes of listening take place, and how they might affect listener engagement, could be highly valuable to researchers and producers working in the fields of object-based and personalized media. Methods An online questionnaire on listening habits and behaviors was distributed to a sample of 264 podcast listeners. An exploratory factor analysis was run to identify factors of environmental context that influence attentional engagement in podcast listening experiences. Five aspects of podcast listening engagement were also defined and measured across the sample. Results The exploratory factor analysis revealed five factors of environmental context labeled as: outdoors, indoors & at home, evenings, soundscape & at work, and exercise. The aspects of podcast listening engagement provided a comprehensive quantitative account of contemporary podcast listening experiences. Discussion The results presented support the hypothesis that elements of a listener's environmental context can influence their attentional engagement in podcast listening experiences. The soundscape & at work factor suggests that some listeners actively choose to consume podcasts to mask disturbing stimuli in their surrounding soundscape. Further analysis suggested that the proposed factors of environmental context were positively correlated with the measured aspects of podcast listening engagement. The results are highly pertinent to the fields of podcast studies, mobile listening experiences, and personalized media, and provide a basis for researchers seeking to explore how other forms of listening context might influence attentional engagement.